The Asia Foundation's motion-picture project and the cultural Cold War in Asia (Film history, 2017)
From the study of material held at the Hoover Institution Archives and the Robert Blum Papers at Yale University Library, the author investigates the activities of the Asia Foundation in the film industries of Asian countries during the Cold War era. The main aims of the Foundation were to support anti-communist personnel wherever possible.
https://katalog.adlr.link/Record/ai-68-OLC1997995662